The paradox of youth violence - Spencer, J. William (Boulder, CO : Lynne Rienner Publishers, 2011)
Is a teenage violent offender a dangerous predator -- or a vulnerable innocent that we should rescue from a life of crime? J. William Spencer probes our ambivalent response to youth violence to show how deeply entwined issues of crime, age, race, and class distort our understanding of an important social problem. Spencer's pointed yet nuanced analysis traces how misconceptions about youth violence -- whether in the form of gangs, school violence, "superpredators," or cyberbullying -- take root in our national consciousness and undercut our attempts to remedy the problem. Equally, it offers a new understanding both of the nature of juvenile delinquency and of the role of cultural politics in shaping criminal justice and social services policy. -- Publisher description.
The problem of youth violence -- Constructing the problem -- The search for explanations and solutions -- The drama of iconic narratives -- Lessons learned -- Confronting today's challenges.
Includes bibliographical references and index.
Keywords: Juvenile delinquency -- United States; Youth and violence; Mass media and youth; Juvenile delinquency -- United States -- Prevention; Juvenile delinquency; Juvenile delinquency -- Prevention; Mass media and youth; Youth and violence; United States